Endogenous Activation of Group-I Metabotropic Glutamate Receptors Is Required for Differentiation and Survival of Cerebellar Purkinje Cells - Catania, M. V. (J Neurosci, 2001)
We have applied subtype-selective antagonists of metabotropic glutamate (mGlu) receptors mGlu1 or mGlu5 [7-(hydroxy-imino) cyclopropa[b]chromen-1a-carboxylate ethyl ester (CPCCOEt) or 2-methyl-6-(phenylethynyl)pyridine (MPEP)] to mixed rat cerebellar cultures containing both Purkinje and granule cells. The action of these two drugs on neuronal survival was cell specific. Although CPCCOEt (1, 10, 30 μm) reduced the survival of Purkinje cells, MPEP (3 or 30 μm) selectively reduced the survival of granule cells. Both effects required an early exposure of cultures to antagonists [from 3 to 6 d in vitro (DIV) for CPCCOEt, and from 3 to 6 or 6 to 9 DIV for MPEP]. Addition of MPEP from 6 to 9, 9 to 13, or 13 to 17 DIV also induced profound morphological changes in the dendritic tree and dendritic spines of Purkinje cells, suggesting that endogenous activation of mGlu5 receptors is required for the age-dependent refinement of Purkinje cell phenotype. In in vivo studies, an early blockade of mGlu1 receptors induced in rats by local injections of LY367385 (20 nmol/2 μl), local injections of mGlu1 antisense oligonucleotides (12 nmol/2 μl), or systemic administration of CPCCOEt (5 mg/kg, s.c.) from postnatal day (P) 3 to P9 reduced the number and dramatically altered the morphology of cerebellar Purkinje cells. In contrast, mGlu5 receptor blockade induced by local injections of antisense oligonucleotides reduced the number of granule cells but also produced substantial morphological changes in the dendritic tree of Purkinje cells. These results provide the first evidence that the development of cerebellar neurons is under the control of mGlu1 and mGlu5 receptors, i.e., the two mGlu receptor subtypes coupled to polyphosphoinositide hydrolysis.